Reorientasi Peran Warga dalam Pencegahan Kejahatan Penipuan yang Meresahkan Masyarakat - Handoyo Prasetyo; Bambang Waluyo; Subakdi Subakdi; Anni Alvionita Simanjuntak; Edward Benedictus Roring; Alifio Kadafi; Muhammad Damar Setyo Kumoro (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The increasing number of fraud cases that harm the community is a serious concern. Fraudsters commit crimes with various modes of operation, such as Bodong Investment, giveaways, auctions, online fraud, and job vacancy fraud. The community not only experiences material losses in the form of losing a large amount of money, or losing invested capital, but also experiences psychological losses, and reputation. This community service activity initiates proactive efforts to overcome this problem by reorienting the role of citizens as the front line in preventing crime. By involving the academic community of the Faculty of Law, UPN Veteran Jakarta, this activity seeks to provide a comprehensive understanding of various fraud modes of operation, as well as effective prevention strategies. In addition, this activity also aims to strengthen the sense of ownership and responsibility of citizens towards their environment, as a real manifestation of the spirit of defending the country.